Association Between Coffee Consumption and Visceral Obesity: A Cross-Sectional Study - Yoshinori Hayashi; Noriko Sasabe; Hiroshi Taniguchi; Toshiaki Gunji (Obesities)
Objective: To investigate the association between coffee consumption and visceral obesity (VO). Methods: We conducted a retrospective, cross-sectional, observational study using data from 45,630 participants who underwent a general health check-up program at a medical center in Japan between 2015 and 2018. After excluding participants with missing data or duplicated visits, 19,253 subjects were included in the final analysis. Visceral fat area (VFA) was measured using computed tomography (CT), and data on metabolic disorders, history of lifestyle-related diseases, coffee consumption, and other lifestyle factors were collected via a self-administered questionnaire. Results: The mean ± SD VFA was 74.0 ± 49.7 cm2, and the mean ± SD age was 53.3 ± 9.8 years. The prevalence of VO (VFA ≥ 100 cm2) was 25.5%. The mean coffee consumption was 1.7 ± 1.3 cups per day. In multivariate logistic regression analysis, coffee consumption was significantly inversely associated with VO. Compared to non-coffee drinkers, the odds ratios (ORs) for VO were as follows: 1 or 2 cups/day (OR: 0.75, 95% confidence interval [CI]: 0.68–0.83), 3 or 4 cups/day (OR: 0.67, 95% CI: 0.59–0.75), and ≥5 cups/day (OR: 0.65, 95% CI: 0.53–0.80). In multiple linear regression analysis, coffee consumption was significantly associated with lower VFA (Model 3: β = −1.86, SE = 0.230, p < 0.05). Conclusions: Coffee consumption was significantly associated with lower VO.